Fostering Green Strategy Through "A-F-F-I-R-M" Model For Sustainable Development Within The Environmental - Socio - Economic System In Malaysia - Abu Bakar, Kamarudin; Rajiani, Ismi; Ayob, Md Razali; Nasri, Noor Shawal (2011)
A-F-F-I-R-M is the holistic approach taken by the Malaysian government in completing an ecosystem for environmental sustainability. It expresses the commitment of all stakeholders toward sustainable development in Malaysia. Thus, it is necessary to complete the ecosystem into one that achieves satisfactory levels of environmental sustainability. Hence, this research intends to explore the suitability adoption of A-F-F-I-R-M within the Foresight Model of the environmental-socio-economic dimension of Malaysian, in which the outcome of the research is important as it can determine whether we (the "actors") would all be able to work together to foster green technology as well as extending this call to the world largely and collectively, changing the landscape of the earth for the betterment of future generations. For this reason, the Author(s) has proposed a refine research framework for more effective study of the issue.